The Relationship Between Age and the Morphology of the Crystalline Lens, Ciliary Muscle, Trabecular Meshwork, and Schlemm’s Canal: An in vivo Swept-Source Optical Coherence Tomography Study - Li, Zhangliang; Meng, Ziqi; Qu, Wenyong; Li, Xiuyuan; Chang, Pingjun; Wang, Dandan; Zhao, Yune (Frontiers in Physiology, 2021)
Purpose: To evaluate the effects of age on the morphologies of the crystalline lens, ciliary muscle (CM), Schlemm’s canal (SC), and trabecular meshwork (TM) using swept-source optical coherence tomography (SS-OCT). Methods: Images of the crystalline lens and iridocorneal angle were obtained in healthy participants’ eyes using SS-OCT. Morphological parameters of the crystalline lens, CM, and TM/SC were measured, and the relationship between these parameters and age was evaluated. Results: A total of 62 healthy participants were enrolled, with an age range of 7–79 years. With adjustments for the effects of axial length and sex, both the nasal and temporal SC cross-sectional areas (CSA) and the cross-sectional area of the CM (CMA), distance from the scleral spur to the inner apex of the ciliary muscle (IA-SS), and nasal SC volume were negatively correlated with age (P ≤ .041). Meanwhile, the lens thickness (LT) (P < .001) and lens vault (LV) (P < .001) were positively correlated with age, and the radius of the curvature of the anterior lens (ALR) was negatively correlated with age (P < .001). Conclusion: Increasing age was associated with a thicker crystalline lens, a steeper anterior lens curvature, an anteriorly located and smaller CM, and a narrower SC.